PENGEMBANGAN MEDIA PEMBELAJARAN KARTU OPI (OPERASI PERKALIAN DAN PEMBAGIAN) FLIP DI SEKOLAH DASAR - Irfan Abdul Azis; Chusna Apriyanti; Wulan Trisnawaty (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research aims to develop the OPI FLIP card learning tool for multiplication and division operations for third grade students at SD Negeri 1 Karanggede, as well as to determine its feasibility based on expert assessment and trials by teachers and students. This research is a development study (Research and Development) using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 1 teacher and 16 students from class III at SD Negeri 1 Karanggede. Data collection techniques include observation, interviews, expert validation, questionnaires, and documentation. Meanwhile, data analysis is conducted thru expert validation and product testing. The research results indicate that the developed media is suitable for use, with feasibility percentages from subject matter experts at 89%, media experts at 80%, language experts at 92.2%, individual trials at 82.6%, limited trials at 92.3%, field trials at 88.9%, and teacher feasibility trials at 97.3%. The research results affirm that the OPI FLIP card learning tool designed can be utilized and serves as a solution in the teaching process of Mathematics at the elementary school level.